Are brood sex ratios adaptive?—The effect of experimentally altered brood sex ratio on nestling growth, mortality and recruitment. (14th November 2022) - Szász, Eszter; Sarkadi, Fanni; Szöllősi, Eszter; Kopena, Renáta; Török, János; Rosivall, Balázs
Abstract: Brood sex ratios (BSRs) have often been found to be nonrandom in respect of parental and environmental quality, and many hypotheses suggest that nonrandom sex ratios can be adaptive. To specifically test the adaptive value of biased BSRs, it is crucial to disentangle the consequences of BSR and maternal effects. In multiparous species, this requires cross‐fostering experiments where foster parents rear offspring originating from multiple broods, and where the interactive effect of original and manipulated BSR on fitness components is tested. To our knowledge, our study on collared flycatchers ( Ficedula albicollis ) is the first that meets these requirements. In this species, where BSRs had previously been shown to be related to parental characteristics, we altered the original BSR of the parents shortly after hatching by cross‐fostering nestlings among trios of broods and examined the effects on growth, mortality and recruitment of the nestlings. We found that original and experimental BSR, as well as the interaction of the two, were unrelated to the fitness components considered. Nestling growth was related only to background variables, namely brood size and hatching rank. Nestling mortality was related only to hatching asynchrony. Our results therefore do not support that the observed BSRs are adaptive in our study population. However, we cannot exclude the possibility of direct effects of experimentally altered BSRs on parental fitness, which should be evaluated in the future. In addition, studies similar to ours are required on various species to get a clearer picture of the adaptive value of nonrandom BSRs. Abstract : Brood sex ratios (BSRs) are often found to be nonrandom in respect of parental or environmental quality, and this phenomenon is assumed to be adaptive, although experimental studies on the fitness consequences of BSRs are scarce. We conducted a cross‐fostering experiment in collared flycatchers to reveal the effects of original and manipulated BSRs on the fitness components of the nestlings. As neither the original nor the manipulated BSRs were related to offspring performance, we found no evidence of adaptive sex ratio adjustment in our study population.